2005
DOI: 10.1073/pnas.0506125102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seasonal climate forecasts and participatory workshops among subsistence farmers in Zimbabwe

Abstract: Improvements in the ability to model El Niñ o and other large-scale interannual climate variations have allowed for the development of seasonal climate forecasts, predicting rainfall and temperature anomalies for many places around the world. These forecasts have allowed developing countries to predict shortfalls in grain yields, with benefits for food security. Several countries communicate the forecasts to subsistence farmers, which could allow them to mitigate the effects of drought on their harvests by ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
120
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(129 citation statements)
references
References 14 publications
9
120
0
Order By: Relevance
“…A case study approach was used for the empirical study of Lower Gweru Irrigation Figure 1. Zimbabwe Agroecological Regions and Lower Gweru Location (after Patt et al 2005) Peasant farming is practised in most parts of the area. Crops commonly are grown ranges from the staple food maize, sweet potatoes and small grain crops being grown as a buffer for semi-arid conditions that prevail in the area.…”
Section: Introductionmentioning
confidence: 99%
“…A case study approach was used for the empirical study of Lower Gweru Irrigation Figure 1. Zimbabwe Agroecological Regions and Lower Gweru Location (after Patt et al 2005) Peasant farming is practised in most parts of the area. Crops commonly are grown ranges from the staple food maize, sweet potatoes and small grain crops being grown as a buffer for semi-arid conditions that prevail in the area.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cane et al (22) showed that Ͼ60% of the variance in Zimbabwean maize yield could be accounted for by an index of ENSO and that accurate predictions of yield could be made with lead times of up to 1 year. Because of the predictable association between ENSO and African climate, ENSO information is being used with other information to forecast and mitigate climatic impacts on water supplies, food production, and human health in southern and eastern Africa (23)(24)(25). We believe that such use of ENSO and NAO information could be even more fruitful if the link between these indices and food production is empirically assessed at large spatial scales.…”
mentioning
confidence: 99%
“…Some research findings have indicated the usefulness of weather forecasts for reducing vulnerability of rain-fed agriculture to drought, flooding and extremely low or high temperature [22][23][24][25][26]. Initiatives to promote access of African farmers to weather forecasts include formation of several regional Climate Outlook Forums (COFs) in the late 1990s [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%